2018
DOI: 10.1080/00405000.2018.1460039
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and graphene oxide-coated polyamide monofilament yarns for fiber-shaped flexible electrodes

Abstract: In this study, polyamide monofilament yarn of 3000 tex was coated with graphene oxide (GO) nanomaterial using dip-coating method. The graphene oxide layer was then reduced with green chemical reduction method, resulting in a reduced graphene oxide-coated monofilament yarn. The properties of the graphene oxide and reduced graphene oxide-coated polyamide monofilament yarns were characterized by performing physical, electrical, optical, and morphological investigations. The lowest sheet resistance was measured fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 43 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Tas et al produced graphene and graphene oxide-coated polyamide monofilament yarns for fiber-shaped flexible electrodes. The electrical and optical properties of monofilament yarns were measured [7].…”
Section: Introduction *mentioning
confidence: 99%
“…Tas et al produced graphene and graphene oxide-coated polyamide monofilament yarns for fiber-shaped flexible electrodes. The electrical and optical properties of monofilament yarns were measured [7].…”
Section: Introduction *mentioning
confidence: 99%
“…The electrochemical exfoliation method reported by Feng, Müllen, and co-workers [1] demonstrated that electrochemically exfoliated graphite provides graphene flakes from one to three layers with a high yield of >80%, a high C/O ratio of~12, a sheet resistance value of 4.8 kΩ•m −1 , and hole mobility of 233 cm 2 •V −1 •s −1 for a single sheet [1]. Currently, solution process methods of graphene and GO materials also receive considerable attention, mainly including spin coating, dip coating, and drop casting [73][74][75][76][77][78]. A comparison of these approaches is shown in Table 2.…”
Section: Graphenementioning
confidence: 99%
“…[ 4 , 6 ] When applied practically, the nanosized graphene particles always need to be assembled together as certain format of macrostructures to support key structures and functions for various smart devices and systems, such as working electrodes of micro‐supercapacitors and sensing elements of flexible electronics. [ 7 , 8 ] In comparison with 1D (e.g., graphene‐based filaments, yarns, and composite fibers) [ 9 , 10 , 11 ] and 2D (e.g., graphene‐based thin films, papers, and fabrics) [ 12 , 13 ] geometries with small, thin, and/or binder/substrate‐supported natures, the graphene‐based 3D aerogels, [ 14 ] hydrogels, [ 15 ] foams, [ 16 ] millispheres, [ 17 ] and laminated structures/composites [ 18 , 19 ] were also intriguingly focused as another important macroscopic ensembles, exhibiting multiple unique characteristics including free‐standing and/or binder‐free structures, widely scaled and highly designable configurations, and organized networking architectures with interconnected nanoparticles/ domains. [ 20 ] Hence, the building of macroscopic 3D graphene has become a significant topic for satisfying the continuously upgraded structures and functions in various novel devices, such as artificial skins and muscles, wearable electronics, biomimetic surfaces, thin‐film batteries, and soft robots.…”
Section: Introductionmentioning
confidence: 99%